Cost–Benefit Analysis of China’s Whole County PV Program: A Case Study of Julu County, Hebei Province - Wen Jiang (Journal of World Economy, 2023)
Solar photovoltaics’ rising efficiency is increasingly considered the key to achieving carbon neutrality targets in various countries. The Chinese government implemented a variety of regulations from both the supply and demand sides to assist in the development of distributed photovoltaics in the second decade of the twenty-first century. The whole county-wide photovoltaic promotion project, announced in 2021, is regarded as one of the most important new energy development projects in China in the coming years. The paper examines the cost and benefits of a pilot whole-county distributed photovoltaics project in Julu County, Hebei Province, from the perspectives of different stakeholders. The analysis shows that as China enters the era of grid parity, the whole county’s distributed photovoltaics programme still exhibits robust economic, social, and environmental performance in locations with abundant solar resources. And different business models have a significant impact on the distribution of interests among stakeholders. The goal of this paper is to offer effective policy recommendations for promoting the development of distributed new energy beyond urban areas.